2001
DOI: 10.1007/s005200000221
|View full text |Cite
|
Sign up to set email alerts
|

Manifest Anxiety Scale for evaluation of effects of granisetron in chemotherapy with CDDP and 5FU for head and neck cancer

Abstract: The level of anxiety was examined before treatment by means of the Manifest Anxiety Scale (MAS) in 41 patients with squamous cell carcinoma of the head and neck. They received 5 days of neoadjuvant chemotherapy with cisplatin (CDDP) and 5-fluorouracil (5FU). Granisetron (KYT) was administered daily from day 1 to day 5. Nausea, vomiting, appetite, and well-being were assessed during and after chemotherapy. The relation between the effects of KYT and anxiety was studied. Seventeen patients were proven to have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In the present study however, there was no other group to compare proportion of patients with anxiety and depression. Granisetron an antiemetic has also been found to be less effective in patients with manifest anxiety [ 11 ]. Effect of age has been evaluated and older patients and men had been found to have less anxiety and depression [ 12 ], we however failed to find any such relation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study however, there was no other group to compare proportion of patients with anxiety and depression. Granisetron an antiemetic has also been found to be less effective in patients with manifest anxiety [ 11 ]. Effect of age has been evaluated and older patients and men had been found to have less anxiety and depression [ 12 ], we however failed to find any such relation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since absorption has been suggested to be a potential risk factor for both anxiety disorders [32] and somatic symptoms [30, 31], and since trait anxiety has been shown to be associated with the severity of side effects [43], we specifically explored the possible influence of trait anxiety on the associations between side effects and the three remaining trait measures. The associations found between side effects and sensory amplification and autonomic perception ceased to be significant when controlling for trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have observed that anxiety symptoms are related to delayed emesis and poorer response to anti-nausea medication after use of platinum-based chemotherapy. 10 …”
Section: Introductionmentioning
confidence: 99%